2020
DOI: 10.1108/jeas-07-2019-0073
|View full text |Cite
|
Sign up to set email alerts
|

Human capital and economic growth in OECD countries: some new insights

Abstract: PurposeThe new growth literature in general is very optimistic about the positive impact that human capital has on the economic growth of countries. Based on this argument, the current paper focusses to investigate the impact of different types of human capital on economic growth.Design/methodology/approachThe paper utilizes data for the period 1998 to 2017 and employs suitable econometric techniques.FindingsIt is found that it is not the stock of human capital rather its utilization in terms of average workin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 43 publications
1
15
0
1
Order By: Relevance
“…Gruzina et al. , 2021; Nathaniel, 2021; Tahir et al. , 2020; Cuevas Ahumada and Calderón Villarreal, 2019; Pelinescu, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gruzina et al. , 2021; Nathaniel, 2021; Tahir et al. , 2020; Cuevas Ahumada and Calderón Villarreal, 2019; Pelinescu, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many scientific studies have suggested the positive effect of human capital on economic growth (e.g. Gruzina et al, 2021;Nathaniel, 2021;Tahir et al, 2020;Cuevas Ahumada and Calder on Villarreal, 2019;Pelinescu, 2015). Although the concept of human capital is limited to education (Adejumo et al, 2021;€ Ozdo gan € Ozbal, 2021;Ranjan, 2020;Burgess, 2016;Adedeji and Campbell, 2013), in the growth literature some are regarding health as another fundamental element of human capital (Hatak and Zhou, 2021;Thinagar et al, 2021;Zhao and Du, 2021;Currie, 2020;Parro and Pohl, 2018;Churchill et al, 2015;Barro, 2013;Bloom et al, 2001;Mushkin, 1962;Schultz, 1961).…”
Section: Introductionmentioning
confidence: 99%
“…Human capital is a concept that first appeared in 1776 in classical economics [6]. From a production orientation perspective, Romer in Tariq et al, states that human capital is a fundamental source of economic productivity [7]. Rosen and Gayer had a similar opinion states that human capital is an investment made by humans to increase their productivity [8].…”
Section: Human Resources Investmentmentioning
confidence: 99%
“…When investment is inadequate to ensure the attainment of full employment, borrowing and spending by the government leads to an increase in public investment which complements the inadequate private investment to stimulate economic growth and recover. Moreover, Tahir et al (2020) examined that human capital, trade openness and public investment are positively associated with economic growth for developing countries. The study also revealed that human capital accumulation has positively impacted economic growth.…”
Section: Public Debtmentioning
confidence: 99%
“…Because risk management on public debt may influence both debt level and debt composition and to both the micro and macro country, developing framework both short and long term. On the other hand, Tahir et al (2020) examined that human capital and public investment are positively associated with economic growth including that human capital accumulation for developing countries.…”
Section: Regression Modelmentioning
confidence: 99%